2013
DOI: 10.3109/17549507.2013.763290
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the collaborative clinical education model to inform speech-language pathology practice

Abstract: A shortage of clinical education placements for allied health students internationally has led to the need to explore innovative models of clinical education. The collaborative model where one clinical educator supervises two or more students completing a clinical placement concurrently is one model enabling expansion of student placements. The aims of this review were to investigate advantages and disadvantages of the collaborative model and to explore its implementation across allied health. A systematic sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 25 publications
1
50
0
Order By: Relevance
“…In the case of benefits for student learning, much has been written about the paired‐placement model (Baldry Currens and Bithell , DeClute and Ladyshewsky , O'Connor et al . , Dawes and Lambert , Briffa and Porter ). In the case of the latter, there is much still to learn (Rodger et al .…”
Section: Introductionmentioning
confidence: 97%
“…In the case of benefits for student learning, much has been written about the paired‐placement model (Baldry Currens and Bithell , DeClute and Ladyshewsky , O'Connor et al . , Dawes and Lambert , Briffa and Porter ). In the case of the latter, there is much still to learn (Rodger et al .…”
Section: Introductionmentioning
confidence: 97%
“…Having two students together lends itself to pairing and collaboration among students, which makes the learning experience more optimal [6]. Moreover, investigators have reported that offcampus clinical educators are receptive to implementation of the collaborative model and that the model has been beneficial with placement shortages [4,7].…”
Section: Community-based Models Of Clinical Educationmentioning
confidence: 99%
“…Many graduate SLP programs, for example, are experiencing a shortage of quality clinical supervisors [4]. In an effort to provide better clinical placement experiences for graduate students, university programs and community partners have begun to explore other solutions.…”
Section: Community-based Models Of Clinical Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative models have much to offer CEs in contemporary practice. For example, the collaborative model assigns multiple students to each educator, providing opportunities for peer-assisted learning and aiding educators balance their professional and educative duties (Briffa & Porter, 2013). Nonetheless, "much of the resistance or inability to adopt new approaches to clinical education lies with inadequate preparation and support of CEs" (McAllister, 2005, p. 145).…”
Section: Introductionmentioning
confidence: 99%